2015
DOI: 10.1007/s11581-015-1441-z
|View full text |Cite
|
Sign up to set email alerts
|

Facile synthesis of polyaniline/NiCo2O4 nanocomposites with enhanced electrochemical properties for supercapacitors

Abstract: A b s t r a c t P o l y a n i l i n e / N i C o 2 O 4 nan oco mpos ites (PANI/NiCo 2 O 4 ) with different amounts of NiCo 2 O 4 (5, 8, 10, 15, and 20 wt%) were prepared via in situ chemical oxidation polymerization in the presence of the NiCo 2 O 4 particles, while the NiCo 2 O 4 nanoparticles were synthesized by a modified sol-gel method. The structure and morphology of PANI/NiCo 2 O 4 nanocomposites were characterized by Fourier transform infrared (FT-IR), X-ray diffraction (XRD), and scanning electron micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(12 citation statements)
references
References 45 publications
0
12
0
Order By: Relevance
“…One is 1380 cm −1 , attributed to the asymmetric stretching vibrations of TdOOh. TdOOh is the oxygen‐containing chemical bond connecting the tetrahedron and the octahedron structures of NiCo 2 O 4 lattice . The other is the typical metal‐oxygen vibrations of NiCo 2 O 4 at 650 and 560 cm −1 , respectively .…”
Section: Methodsmentioning
confidence: 99%
“…One is 1380 cm −1 , attributed to the asymmetric stretching vibrations of TdOOh. TdOOh is the oxygen‐containing chemical bond connecting the tetrahedron and the octahedron structures of NiCo 2 O 4 lattice . The other is the typical metal‐oxygen vibrations of NiCo 2 O 4 at 650 and 560 cm −1 , respectively .…”
Section: Methodsmentioning
confidence: 99%
“…For all electrodes, absorption bands observed at around 1020 cm -1 (-CO), 1110 cm -1 (-COOH), 1640 cm -1 (-C=O), 2855 cm -1 (-CH), 2918 cm -1 (-CH), and 3377 cm -1 (-OH), belong to stretching vibrations of hydroxyl and carboxyl groups 48 The absorption band of C-H bending peaks for PANI shifts to higher peak positions in PANI-Co 3 O 4 -GF, which suggests a strong interaction between interweaved PANI and Co 3 O 4 nanostructures on GF 42 . Further, the broadening of the peak at 1306 cm -1 confirms the formation of a coordination compound between cobalt ions and amine/imine-nitrogen groups of PANI and enhanced charge delocalization on PANI with the incorporation of transition metal ions 50 . SEM images of the four electrodes show structure changes.…”
Section: Physicochemical Characterizations Of the Anodes Developedmentioning
confidence: 75%
“…It is further observed that the NCO/rGO/PANI and NCO/N-rGO/PANI nanocomposites show all the characteristic bands of PANI. For these two electrode materials, the stretching band at ∼3266 cm –1 is assigned to the N–H stretching vibration, the band at ∼2927 cm –1 is associated with the C–H stretching vibration, and the bands at ∼1582 and 1498 cm –1 are assigned to the quinoid and benzenoid stretching vibration, respectively . Further, the bands at 1291 and 1235 cm –1 correspond to the C–N stretching vibration of the quinoid and benzenoid rings.…”
Section: Results and Discussionmentioning
confidence: 96%
“…For these two electrode materials, the stretching band at ∼3266 cm −1 is assigned to the N−H stretching vibration, the band at ∼2927 cm −1 is associated with the C−H stretching vibration, and the bands at ∼1582 and 1498 cm −1 are assigned to the quinoid and benzenoid stretching vibration, respectively. 42 Further, the bands at 1291 and 1235 cm −1 correspond to the C−N stretching vibration of the quinoid and benzenoid rings. On the other hand, the characteristic bands at 1137 cm −1 and 845 cm −1 are associated with the C−H in-plane and out-of-plane bending vibrations, respectively.…”
Section: Methodsmentioning
confidence: 97%